EFEK SUHU PENGERINGAN PADA KARAKTERISTIK FISIKOKIMIA, KADAR SENYAWA FENOLIK TOTAL DAN PENILAIAN SENSORI DARI PENERIMAAN KONSUMEN PADA TEH HERBAL PARE (Momordica charantia) - Kamarudin, Anna Permatasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2019)
ABSTRACT The effect drying temperature on physicochemical characteristics and consumer acceptance on sensory evaluation on bitter gourd (Momordica charantia) herb teas were carried out. This research to determined of drying temperature on physicochemical characteristics and consumer acceptance on sensory evaluation. The slice of bitter gourd dried at 3 types of temperatures, 40oC, 50oC and 60oC. Control of sample used bitter gourd (Momordica charantia) herbs tea and green (Camellia sinensis) tea commercial. Measurement of colour used Minolta CR-300 Chromameter. The pH determined used a glass electrode pH meter. Titratable Acidity of samples evaluated using method of AOAC (2000). Overall colour of samples for brightness (L), were 33,0-35, 0; Redness (a), were 2,7-3,0; and yellowness (b), were between -2 and -3. Meanwhile, the samples of pH were between 2,7-3,0. The Titratable Acidity of samples between 2,7-3,1%. Brightness evaluated all of samples showed no significant different (p>0,05). The pH of sample with drying of temperature at 40oC showed no significant different (p>0,05) compared to two samples control. Titratable acidity all of samples showed no significant different (0>0,05). The highest of Total phenolic content was T50. The attributes sensory evaluation on consumer acceptance, were bitterness and ‘aftertaste’ all of samples showed no significant different (p>0,05) among the commercial samples . However, the other attributes (colour, aroma, and overall acceptability) showed significant different (p<0,05) and showed better on commercial samples. Keywords: bitter gourd, temperature, physicochemical, phenolic, sensory evaluation